Hubungan Personal Hygiene dengan Kejadian Kusta di Wilayah Kerja Puskesmas Nania Kota Ambon - M Fadly Kaliky; Rahma Tunny (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Leprosy is an infectious disease that can attack the skin, caused by the bacterium Mycobacterium leprae. Leprosy is an infectious disease with a long incubation time of up to many years. The purpose of this study is to analyze the relationship between personal hygiene and the incidence of leprosy in the working area of the Nania Health Center, Ambon City. Methodology: In this study, the researcher used a quantitative research method with a case control approach. The population and sample were all leprosy patients, namely 21 case respondents and 21 control respondents. Data collection uses questionnaires. Data analysis using the Chi-square Test. Results: The results showed that there was a significant relationship between independent variables, namely bathing habits (p-value = 0.04), towel borrowing habits (p-value = 0.000), and the incidence of leprosy. Discussion: The conclusion in this study is that there is a significant relationship between bathing habits, towel borrowing habits, hand and foot washing habits to the incidence of leprosy in Manguharjo and Ngegong Health Centers. Suggestions for Puskesmas are the need for socialization on how to prevent and treat leprosy and provide education about community stigma that leprosy is not a scary disease.